Implementasi Kebijakan Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) di Komunitas Asosiasi Industri Kreatif dan Pelaku Usaha (ASIPA) Tangerang Selatan - Asyifa Permata Dewi; Muhammad Khoirul Anwar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the drivers of the Indonesian economy that have great potential to improve the economy and community welfare. The development of MSMEs, which has so far taken the form of training, technical guidance and entrepreneurship workshops attended by ASIPA members and general MSMEs in the ASIPA Community of South Tangerang City, has had a positive effect on several actors, although not all of them have been able to implement what has been given during the training. This research aims to discuss how the Micro, Small and Medium Enterprises (MSME) Development Policy is implemented in the ASIPA South Tangerang Community, using a qualitative approach with descriptive methods. This research analysis uses the theory put forward by Edward III (1980) with four indicators, namely: (1) Communication, (2) Resources, (3) Disposition, (4) Bureaucratic Structure. The data analyzed is the result of interviews, observations and documentation in the ASIPA South Tangerang Community. The results of research on the Implementation of Micro, Small and Medium Enterprises (MSME) Development Policy in the South Tangerang ASIPA Community from four indicators are that (1) Lack of understanding in promotion to improve the business of MSME actors (2) In providing services, guidance and security for MSME actors in terms of quality, there are still administrators and members who lack competence. Apart from that, in terms of quantity, the number of administrators and members is still minimal to carry out improvement activities in innovation (3) There is still a lack of facilities and training activities as well as proposals for security equipment and others, not all of which can be fulfilled because limited budget resources (4) The administrators and members have carried out their duties in accordance with the SOP that has been regulated, however the performance of the administrators and members has not been optimal because there are still administrators and members who carry out concurrent work in other fields.